2018
DOI: 10.1021/acsami.8b15594
|View full text |Cite
|
Sign up to set email alerts
|

Dual T1/T2 Nanoscale Coordination Polymers as Novel Contrast Agents for MRI: A Preclinical Study for Brain Tumor

Abstract: In the last years, extensive attention has been paid on designing and developing functional imaging contrast agents for providing accurate non-invasive evaluation of pathology in vivo. However, the issue of false-positives or ambiguous imaging and the lack of a robust strategy for simultaneous dual-mode imaging remain to be fully addressed. One effective strategy for improving it is to rationally design magnetic resonance imaging (MRI) contrast agents (CAs) with intrinsic T 1 /T 2 dual-mode imaging features. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 80 publications
0
50
1
Order By: Relevance
“…Based on iron, these contrast agents, the ultimate fate of which is macrophage capture and subsequent metabolism into labile iron, are potentially less toxic than gadolinium based ones. Furthermore, as for many nanomaterials, their surface may be easily modified to offer longer circulating time, multimodality [6], modulable half-life or specificity [7,8], or to offer other functionalities such as drug delivery vehicles or magnetic and photonic ablation therapies [9][10][11], which is otherwise difficult to obtain with molecular contrast agents. However, large doses still need to be injected to afford a significant contrast, which raises toxicity concerns related to iron overload [2].…”
Section: Introductionmentioning
confidence: 99%
“…Based on iron, these contrast agents, the ultimate fate of which is macrophage capture and subsequent metabolism into labile iron, are potentially less toxic than gadolinium based ones. Furthermore, as for many nanomaterials, their surface may be easily modified to offer longer circulating time, multimodality [6], modulable half-life or specificity [7,8], or to offer other functionalities such as drug delivery vehicles or magnetic and photonic ablation therapies [9][10][11], which is otherwise difficult to obtain with molecular contrast agents. However, large doses still need to be injected to afford a significant contrast, which raises toxicity concerns related to iron overload [2].…”
Section: Introductionmentioning
confidence: 99%
“…The r 2 / r 1 is calculated to be ≈5.50, indicating that P‐UDIOC can be used as an ideal T 1 – T 2 dual‐mode CA under UHF. [ 22,24 ] For comparison, we also investigated the imaging performances of a typical GBCA‐based T 1 CA, Gd‐DTPA, and a typical SPION‐based T 2 CA, MION with a hydrodynamic size of ≈20 nm (Figure S7, Supporting Information). The r 2 / r 1 values of Gd‐DTPA and MION are ≈1.29 and ≈29.56, respectively (Figure S8, Supporting Information), which are either too low or too high for T 1 – T 2 dual‐mode imaging.…”
Section: Figurementioning
confidence: 99%
“…The r 2 / r 1 values of Gd‐DTPA and MION are ≈1.29 and ≈29.56, respectively (Figure S8, Supporting Information), which are either too low or too high for T 1 – T 2 dual‐mode imaging. [ 22,24 ]…”
Section: Figurementioning
confidence: 99%
“…24,25 Previous studies have focused on the physicochemical property of metal unit in coordination polymers, such as magnetic properties for MRI imaging and Fenton activity for chemo-dynamic therapy. [26][27][28][29] However, metal ions detached from the intrinsically biodegradable coordination polymers would also take part in life processes, especially the immune system. [30][31][32] For instance, it has recently been reported that manganese ions and zinc ions could greatly enhance the Cyclic GMP-AMP synthase-stimulator of interferon genes (cGAS-STING) pathway, and subsequently triggers multifaceted type I interferon-driven inflammatory responses to activate innate immune.…”
Section: Introductionmentioning
confidence: 99%